2014
DOI: 10.1016/j.neuroimage.2013.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Competitive mechanisms in sentence processing: Common and distinct production and reading comprehension networks linked to the prefrontal cortex

Abstract: Despite much interest in language production and comprehension mechanisms, little is known about the relationship between the two. Previous research suggests that linguistic knowledge is shared across these tasks and that the left inferior frontal gyrus (LIFG) may be commonly recruited. However, it remains unclear the extent to which production and comprehension share competition mechanisms. Here we investigate this issue and specifically examine competition in determining the event roles in a sentence (agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 127 publications
1
34
0
Order By: Relevance
“…Cells C-D show that the animacy of what is being discussed is also crucial: When speakers are describing something inanimate like policy (cell C), the long-dependency object-extractions and the short-dependency subject-extractions are equally favored and have equal initiation latencies (Montag & MacDonald, 2014). Humphreys and Gennari (2014), holding dependency distance constant, found that both initiation latency and production errors varied with the animacy of the head of the clause (reporter vs. policy). The one lexical combination in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cells C-D show that the animacy of what is being discussed is also crucial: When speakers are describing something inanimate like policy (cell C), the long-dependency object-extractions and the short-dependency subject-extractions are equally favored and have equal initiation latencies (Montag & MacDonald, 2014). Humphreys and Gennari (2014), holding dependency distance constant, found that both initiation latency and production errors varied with the animacy of the head of the clause (reporter vs. policy). The one lexical combination in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, it is possible that competitive mechanisms do not take place in a single brain region but rather take place across more complex brain networks, and information flow within the network may be partially shared across various tasks. Indeed, several studies suggest more than one brain region might be involved in competition resolution (Duncan, 2010;Fuster, 2001;Gennari, MacDonald, Postle, & Seidenberg, 2007;Humphreys & Gennari, 2014). Although more research is surely needed to understand the cognitive and neural processes instantiating competition resolution, the present results suggest possible competitive mechanisms shared across tasks and new avenues for further research.…”
Section: Implications For Models Of Production and Comprehensionmentioning
confidence: 68%
“…Critically, when processing relative clauses, which increase processing load and engender competition, both production and comprehension show common prefrontal activity within Broca s area, in addition to task-specific regions (Humphreys & Gennari, 2014). Specifically, when comparing production and comprehension of relative clauses with the methods and materials used in Studies 1 and 2, semantic similarity was found to positively correlate with the activity within this region (Humphreys & Gennari, 2014;Humphreys, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations